Rancang Bangun Prototipe Alat Pres Tahu Otomatis Berbasis Mikrokontroler - Sumariyah, Sumariyah (BERKALA FISIKA, 2007)
An automatic tahu pressing device prototype that controlled by AT89C51 has been made. The tahu pressing is completed by  the cast with 15 cm length, 10 cm width  and  2,5 cm high. A microcontroller controlled stepper motors move used to make the desiserd shifting of the pressing thickness. One was used to move a conveyor deliver the tahu to be pressed and another to press the tahu itself. The pressing was done by setting the DL value to yield strain. Stepper motors’ step angle was reduced using a gear combination which results in a 0,270 per step. Each stepper motor yields  0,005 mm shifting of the rotating mechanics The prototype of an automatic tahu pressing device that controlled by microcontroller AT89C has done properly, that is automatically pressing tahu according desired  thickness.